AGE AND GROWTH OF POLYDACTYLUS INDICUS (SHAW) - Kagwade, P V (Indian Journal of Fisheries, 2011)
In Polydactylus indicus the scale is in curvilinear relationship with the fish in size. Six rigns are recognised on the scales and these are formed at the fish size of 34.5 cm, S4.S cm, 74.5 cm, 84.5 cm, 94.5 cm, and 104.5 cm respectively. The causes and periodicity of ring formation could not be studied due to the non-availability of material for the whole year. Since the sizes at the first three rings agree with the sizes at ages 1 to 3 obtained from a separate study on the length frequency distribution, it has been presumed that the rings are of an annual nature and hence the above lengths can be taken to represent sizes attained by the 1- through 6-year olds. The growth parameters and growth characteristics of the species have been given.